Mechanosensitive Ion Channel Piezo1 Activated by Matrix Stiffness Regulates Oxidative Stress-Induced Senescence and Apoptosis in Human Intervertebral Disc Degeneration. (10th February 2021) - Wang, Bingjin; Ke, Wencan; Wang, Kun; Li, Gaocai; Ma, Liang; Lu, Saideng; Xiang, Qian; Liao, Zhiwei; Luo, Rongjin; Song, Yu; Hua, Wenbin; Wu, Xinghuo; et al.
Abstract : Mechanical stimulation plays a crucial part in the development of intervertebral disc degeneration (IDD). Extracellular matrix (ECM) stiffness, which is a crucial mechanical microenvironment of the nucleus pulposus (NP) tissue, contributes to the pathogenesis of IDD. The mechanosensitive ion channel Piezo1 mediates mechanical transduction. This study purposed to investigate the function of Piezo1 in human NP cells under ECM stiffness. The expression of Piezo1 and the ECM elasticity modulus increased in degenerative NP tissues. Stiff ECM activated the Piezo1 channel and increased intracellular Ca 2+ levels. Moreover, the activation of Piezo1 increased intracellular reactive oxygen species (ROS) levels and the expression of GRP78 and CHOP, which contribute to oxidative stress and endoplasmic reticulum (ER) stress. Furthermore, stiff ECM aggravated oxidative stress-induced senescence and apoptosis in human NP cells. Piezo1 inhibition alleviated oxidative stress-induced senescence and apoptosis, caused by the increase in ECM stiffness. Finally, Piezo1 silencing ameliorated IDD in an in vivo rat model and decreased the elasticity modulus of rat NP tissues. In conclusion, we identified the mechanosensitive ion channel Piezo1 in human NP cells as a mechanical transduction mediator for stiff ECM stimulation. Our results provide novel insights into the mechanism of mechanical transduction in NP cells, with potential for treating IDD.